Ex utero intrapartum treatment for extremely low birth-weight neonates requiring resuscitation at birth - Tai-Ho Hung; Ting-Xuan Huang; T'sang-T'ang Hsieh (Elsevier, 2017)
Objective: Difficulties often encountered during intubation in extremely low birth-weight (ELBW) neonates requiring resuscitation at birth because of the smaller airway and the pressure from the limited number of attempts before hemodynamic instability occurs. Case report: We evaluated two pregnant women at 26 weeks of gestation with premature rupture of membranes and evidence of chorioamnionitis and applied the concept of ex utero intrapartum treatment, which involved delaying cord clamping (DCC) after establishing a secured airway with adequate ventilation during cesarean delivery. The resuscitative procedure was smooth and all three neonates had favorable outcomes at one month of age. Conclusion: When cesarean delivery is indicated in ELBW infants and intubation after birth is anticipated, DCC after establishing a secured airway may help maintain neonatal cardiovascular stability and allow physicians to resolve the technical difficulties of intubation.